2014
DOI: 10.1155/2014/210146
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Cervical Epidural Hematoma with Hemiparesis Mimicking Cerebral Stroke

Abstract: Aim. Spontaneous cervical epidural hematoma (SCEH) is defined as an epidural hematoma that does not have an etiological explanation. The most common site for SCEH is cervicothoracic area. Early diagnosis and treatment are important for prognosis and good results. In this paper, we aimed to present a case who complains of sudden weakness on right extremities imitating cerebral stroke and that neuroimaging reveals spontaneous cervical epidural hematoma. Case. A 72-year-old woman was admitted to our hospital with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…SCEH are a dynamic process that often begin with localized neck pain as blood collects in the epidural space, and can progress to paresthesia, paraplegia, quadriplegia, or hemiparesis as the hematoma expands and subsequently compresses the spinal cord. 2,9 This is the same progression we witnessed in our patient. Taha et al described a 41-year-old man diagnosed with SCEH who presented with six days of neck pain radiating to both upper extremities that subsequently progressed to quadriparesis and urinary urgency.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…SCEH are a dynamic process that often begin with localized neck pain as blood collects in the epidural space, and can progress to paresthesia, paraplegia, quadriplegia, or hemiparesis as the hematoma expands and subsequently compresses the spinal cord. 2,9 This is the same progression we witnessed in our patient. Taha et al described a 41-year-old man diagnosed with SCEH who presented with six days of neck pain radiating to both upper extremities that subsequently progressed to quadriparesis and urinary urgency.…”
Section: Discussionsupporting
confidence: 89%
“…8 Although various causes have been attributed to SCEH, including the use of antithrombotic medications, in as many as 40-50% of the cases the exact cause remains unknown. 2,9 It is likely that the daily low-dose aspirin played a role in our patient.…”
Section: Discussionmentioning
confidence: 96%
“…However, Miyagi et al reported that arterial blood supply is a more persuasive force for pressure inside the venous plexus as it is lower than that in the epidural space. Furthermore, in some cases, rapidly deteriorating neurological deficits after the initial onset of back pain or lumbago indicated a rapid formation of the hematoma and spinal cord compression, which is suggestive of the arterial origin of spontaneous SEH (6).…”
Section: Discussionmentioning
confidence: 99%
“…[5,8] e classical clinical presentation is acute neck or interscapular pain, and as a result of the spinal cord compression sensory and motor loss may be seen, such as paraparesis, quadriparesis, or Brown-Sequard syndrome. [2,14] Although in some cases, a pure motor hemiparesis may be seen and mistaken for cerebrovascular stroke. [14] erefore, early diagnosis and treatment are essential for good prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…[2,14] Although in some cases, a pure motor hemiparesis may be seen and mistaken for cerebrovascular stroke. [14] erefore, early diagnosis and treatment are essential for good prognosis.…”
Section: Introductionmentioning
confidence: 99%